Facile and Rapid Method for Fabricating Liquid Metal Electrodes with Highly Precise Patterns via One-Step Coating - Park, Tae Hwan; Kim, Ju Hyung; Seo, Soonmin (Advanced Functional Materials, 2020)
Gallium-based alloys, which are virtually non-toxic liquid metals at room temperature, are considered highly promising electrode materials for state-of-the-art electronics with new form factors. Herein, a facile and rapid method to fabricate liquid metal electrodes with highly precise patterns via a one-step coating is presented. For this work, polymeric stencil masks with dual structures, comprising upper and lower structures for injecting and molding the liquid metal, respectively, are used for direct patterning of the liquid metal via spray deposition for few seconds, enabling the formation of complex and minute patterns including long thin lines and hollow forms. This method can be adapted to 3D substrates of various materials without any surface treatment, owing to the intrinsic adhesive and flexible properties of the polymeric masks ensuring conformal contact with non-flat surfaces, and is also expected to be applicable to sub-micron patterns. In addition, a number of highly flexible/stretchable electronic applications, exhibiting no change in electrical conductivity upon consecutive structural deformations, are demonstrated on various substrates including human skin. It is anticipated that these results will not only spur the further development of flexible/stretchable electronics, but also significantly contribute to the innovative on-site fabrication of wearable electronics with high durability.
Keywords: Conformal contacts; Direct-patterning; Electrical conductivity; Electrode material; Electronic application; Site fabrication; Structural deformation; Various substrates; liquid metals; soft electronics; soft lithography; spray processes; stencil masks